USING GESTURES: INTENTIONAL TEACHING GESTURES AS AN L2 FACILITATIVE TOOL - Wilks-Smith, Naomi (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
Gestures used for classroom pedagogical purposes, or Intentional Teaching Gestures (ITG), are often used in second language (L2) programs, however, little is known of their impact on L2 learning. This study of students’ use of ITG was carried out to address the impact of ITG on L2 learning in a primary school context. The research approach combined a naturalistic inquiry in a case study school with mixed methods to investigate students’ use of ITG and patterns of use. This article examines the data relating to students’ use of ITG in two oral language tasks. Findings reveal that more students used ITG when orally telling a narrative that had been introduced to them with ITG and when viewing ITG. Students used ITG to demonstrate meaning and to support language retrieval and ITG use often preceded oral production. The findings highlight the cognitive role of ITG in language recall and as the primary mode of communicating meaning when there is a gesture-word mismatch. Learners’ use of ITG provide insights into their stage of language development and their language gaps and are useful as a diagnostic tool for teachers. The findings contribute practical understandings towards language teaching pedagogy and practice.